Alkaline Phosphatase, Soluble Extracellular Adenine Nucleotides, and Adenosine Production after Infant Cardiopulmonary Bypass. - Jesse A Davidson; Tracy Urban; Suhong Tong; Mark Twite; Alan Woodruff; Paul E Wischmeyer; Jelena Klawitter (PLoS ONE)
Rationale Decreased alkaline phosphatase activity after infant cardiac surgery is associated with increased post-operative cardiovascular support requirements. In adults undergoing coronary artery bypass grafting, alkaline phosphatase infusion may reduce inflammation. Mechanisms underlying these effects have not been explored but may include decreased conversion of extracellular adenine nucleotides to adenosine. Objectives 1) Evaluate the association between alkaline phosphatase activity and serum conversion of adenosine monophosphate to adenosine after infant cardiac surgery; 2) assess if inhibition/supplementation of serum alkaline phosphatase modulates this conversion. Methods and research Pre/post-bypass serum samples were obtained from 75 infants <4 months of age. Serum conversion of 13C5-adenosine monophosphate to 13C5-adenosine was assessed with/without selective inhibition of alkaline phosphatase and CD73. Low and high concentration 13C5-adenosine monophosphate (simulating normal/stress concentrations) were used. Effects of alkaline phosphatase supplementation on adenosine monophosphate clearance were also assessed. Changes in serum alkaline phosphatase activity were strongly correlated with changes in 13C5-adenosine production with or without CD73 inhibition (r = 0.83; p<0.0001). Serum with low alkaline phosphatase activity (≤80 U/L) generated significantly less 13C5-adenosine, particularly in the presence of high concentration 13C5-adenosine monophosphate (10.4μmol/L vs 12.9μmol/L; p = 0.0004). Inhibition of alkaline phosphatase led to a marked decrease in 13C5-adenosine production (11.9μmol/L vs 2.7μmol/L; p<0.0001). Supplementation with physiologic dose human tissue non-specific alkaline phosphatase or high dose bovine intestinal alkaline phosphatase doubled 13C5-adenosine monophosphate conversion to 13C5-adenosine (p<0.0001). Conclusions Alkaline phosphatase represents the primary serum ectonucleotidase after infant cardiac surgery and low post-operative alkaline phosphatase activity leads to impaired capacity to clear adenosine monophosphate. AP supplementation improves serum clearance of adenosine monophosphate to adenosine. These findings represent a potential therapeutic mechanism for alkaline phosphatase infusion during cardiac surgery. New and noteworthy We identify alkaline phosphatase (AP) as the primary soluble ectonucleotidase in infants undergoing cardiopulmonary bypass and show decreased capacity to clear AMP when AP activity decreases post-bypass. Supplementation of AP ex vivo improves this capacity and may represent the beneficial therapeutic mechanism of AP infusion seen in phase 2 studies.